2013
DOI: 10.1371/journal.pone.0062395
|View full text |Cite
|
Sign up to set email alerts
|

Citation Analysis May Severely Underestimate the Impact of Clinical Research as Compared to Basic Research

Abstract: BackgroundCitation analysis has become an important tool for research performance assessment in the medical sciences. However, different areas of medical research may have considerably different citation practices, even within the same medical field. Because of this, it is unclear to what extent citation-based bibliometric indicators allow for valid comparisons between research units active in different areas of medical research.MethodologyA visualization methodology is introduced that reveals differences in c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
135
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 204 publications
(153 citation statements)
references
References 39 publications
8
135
1
2
Order By: Relevance
“…In Van Eck et al (2013), the authors had a priori information about this possibility in a number of subject categories within the WoS system. The problem, of course, is that we do not have any information about which clusters may lack the desirable homogeneity within any given classification system.…”
Section: Ii4 Cluster Homogeneity In the Different Classification Symentioning
confidence: 99%
See 1 more Smart Citation
“…In Van Eck et al (2013), the authors had a priori information about this possibility in a number of subject categories within the WoS system. The problem, of course, is that we do not have any information about which clusters may lack the desirable homogeneity within any given classification system.…”
Section: Ii4 Cluster Homogeneity In the Different Classification Symentioning
confidence: 99%
“…On the other hand, using the 20 sections of the Biochemistry heading they clearly illustrate that citation habits vary extensively not only between fields but also within fields. Similarly, Van Eck et al (2013) establish the existence of heterogeneous sub-groups (corresponding to clinical and basic medical research) with different citation practices within WoS subject categories. In this case, the mean citation of an entire category is simply the weighted average of different, and hence non-comparable sub-group mean citations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that researches within the same field have received different extents of attention and thus the number of citations. For example, basic researches had a higher impact than clinical interventional researches 9 . Therefore, the aim of this study is to describe the general landscape of the neuroimaging literature, evaluate performance trends of neuroimaging journals as a whole and to analyse four representative journals with the highest and lowest impact factors (IFs) within this category.…”
mentioning
confidence: 99%
“…This was partly motivated by the simple and rather old-fashioned criterion of consistency: if we are learning things in our research that have bearing on the accuracy and/or legitimacy of the evaluation process, we should bring that knowledge to the evaluation itself rather than pretend that the customary/existing evaluation method is sufficient to realizing the objectives that the evaluators themselves bring to the process. For example, our bibliometric research had shown that citation densities differ considerably within disciplines and the usual normalization of indicators does not correct for those differences (van Eck et al 2013). Because of this, we felt we couldn't really make the claim that the relatively high citation scores of the bibliometric research at our center was in itself already evidence of its high quality.…”
Section: # ! 112mentioning
confidence: 93%